Textiles, identity and innovation : design the future : proceedings of the 1st International Textile Design Conference (D_TEX 2017), November 2-4, 2017, Lisbon, Portugal /: design the future : proceedings of the 1st International Textile Design Conference (D_TEX 2017), November 2-4, 2017, Lisbon, Portugal. (2018) - Unknown
No abstract available